New trends in academic ebooks - Cordón-García, José-Antonio (Anuario ThinkEPI, 2014)
The ebook has established itself in recent years thanks to a confluence of factors. One is the innovations in information technology, which have produced more ergonomic and functional reading devices and changed the reading practices of an important sector of the population. Another is the increased number of titles offered, both general and specialized. In the sciences, these developments have found an increasingly important niche market because of the benefits that electronic publishing provides to improve scientific communication, wherein continuous updating and renewal are very important criteria. Ebooks have given rise to new business and publishing models that have generated a number of trends: open access, unbundling content and publishing on the web, interoperability, editing in the cloud, open proceses, continuous improvements, and the social systems that are integrated into ebook readers.